2006
DOI: 10.1176/ajp.2006.163.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Responses to Continuous Terror: A Study of Two Communities in Israel

Abstract: Continuous terror created similar distress in proximal and remote communities. Exposure to discrete events was not a necessary mediator of terror threat. A subgroup of those exposed developed serious symptoms, whereas others were surprisingly resilient. Disruption of daily routines was a major secondary stressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 16 publications
8
50
2
2
Order By: Relevance
“…Estimates of posttraumatic stress disorder (PTSD) and depression among these populations vary. The following estimates of PTSD have been reported: 7% (Palmieri, Canetti-Nisim, Galea, Johnson, & Hobfoll, 2008), 21% (Shalev, Tuval, Frenkiel-Fishman, Hadar, & Eth, 2006), 26% (Hall et al, 2008), and 27% ). Estimates of depression vary from 17% (Hall et al, 2008) to 59% (Bleich, Gelkopf, & Solomon, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of posttraumatic stress disorder (PTSD) and depression among these populations vary. The following estimates of PTSD have been reported: 7% (Palmieri, Canetti-Nisim, Galea, Johnson, & Hobfoll, 2008), 21% (Shalev, Tuval, Frenkiel-Fishman, Hadar, & Eth, 2006), 26% (Hall et al, 2008), and 27% ). Estimates of depression vary from 17% (Hall et al, 2008) to 59% (Bleich, Gelkopf, & Solomon, 2003).…”
mentioning
confidence: 99%
“…Although the contribution of exposure severity to PTSD is well documented (see Galea, Nandi, & Vlahov, 2005;Neria, Nandi, & Galea, 2008;Norris et al, 2002 for reviews), a number of studies in Israeli populations have not found significant relations between severity of exposure and PTSD (e.g., Besser & Neria, in press;Bleich et al, 2003;Shalev et al, 2006). The longitudinal design of the current study and use of multiple mental health outcomes enabled us to explore these relations, thus extending knowledge of the mental health consequences of exposure to military conflict in a young civilian population.…”
mentioning
confidence: 99%
“…The response may weaken and even disappear, or alternately it may exacerbate such that it causes significant mental, functional and behavioural impairment. 5 Approximately 76 percent of those exposed to a traumatic event will develop at least one possible symptom of acute stress reaction (ASR). Most of these (about 70 percent) will recover with the support of "natural support factors" (their service mates in the division or company).…”
Section: From Combat Stress Reaction To Chronic Post-traumamentioning
confidence: 99%
“…Social support refers to perceived assistance provided by other persons, such as emotional, informational, and tangible assistance (Rosario, Salzinger, Feldman, Ng-Mak 2008). It is a primary interpersonal resource that has been consistently found to be associated with psychological well-being in times of stress, and is generally considered to be a protective factor for individuals who experienced a disaster (Norris et al 2002), terror attack (Hobfoll, Canetti-Nisim, Johnson 2006;Weinberg 2015), or other potentially life-threatening situations (e.g., Norris, Kaniasty 1996;Shalev et al 2006). Research indicates that higher levels of social support serve a protective role, and have also been linked to resilience and recovery with respect to traumatic events (Besser, Priel 2010;Gilbar, Plivazky, Gil 2010;King, King, Foy, Keane, Fairbank 1999).…”
Section: The Relationships Between On Going Terror Attacks Military mentioning
confidence: 99%